2019
DOI: 10.1161/circulationaha.119.041059
|View full text |Cite
|
Sign up to set email alerts
|

HHIPL1 , a Gene at the 14q32 Coronary Artery Disease Locus, Positively Regulates Hedgehog Signaling and Promotes Atherosclerosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Clearly, when the photonic profile of a range of cells in vitro and ex vivo were used as part of a training set by LDA, a substantial proportion of cells within lesions were classified as S100β + vSCs and their SHhderived myogenic progeny. This is not surprising as several previous studies support a role for Hh signalling in vascular lesion formation [20,22,23] where adventitial Sca1 + stem cells colocalise with SHh and its receptor, Ptch1 [48].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Clearly, when the photonic profile of a range of cells in vitro and ex vivo were used as part of a training set by LDA, a substantial proportion of cells within lesions were classified as S100β + vSCs and their SHhderived myogenic progeny. This is not surprising as several previous studies support a role for Hh signalling in vascular lesion formation [20,22,23] where adventitial Sca1 + stem cells colocalise with SHh and its receptor, Ptch1 [48].…”
Section: Discussionsupporting
confidence: 53%
“…When the photonic profile of a range of cells in vitro and ex vivo were deployed as part of a training set using LDA, a substantial proportion of cells within ligated vessels were classified as S100β + vSCs and their SHh-derived myogenic progeny. Several previous lines of evidence point to a role for Hh signalling in vascular lesion formation 30,[75][76][77][78][79][80] . Adventitial Sca1 + stem cells that colocalise with SHh and its receptor, Ptch1 81 contribute to intimal thickening in vivo 77,82,83 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have previously reported that Sonic Hedgehog/Gli signaling plays a key role in atherogenesis (Aravani et al, 2019;Morrow et al, 2007;Redmond et al, 2013), and in regulating proliferation and differentiation of a variety of stem cells (Milla et al, 2012;Mooney et al, 2015). To determine whether Sonic Hedgehog drives the differentiation of S100b+ stem cells to smooth muscle-like cells (i.e., myogenic differentiation) and whether EtOH treatment affects this, S100b + /SM-MHC -/CNN1cells were isolated from mouse thoracic aorta medial explants (Fig.…”
Section: Etoh Inhibits Sonic Hedgehog-induced Myogenic Differentiatiomentioning
confidence: 99%